If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + (12 + c) = 0 Remove parenthesis around (12 + c) 5 + 12 + c = 0 Combine like terms: 5 + 12 = 17 17 + c = 0 Solving 17 + c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + c = 0 + -17 Combine like terms: 17 + -17 = 0 0 + c = 0 + -17 c = 0 + -17 Combine like terms: 0 + -17 = -17 c = -17 Simplifying c = -17
| 12/n=5 | | 328+309= | | -17-(-8)-(-9)= | | -2(-13d-18)+20=-18-17+19d | | 8(1-6x)+2=346 | | 4x+10+3x+6=180 | | 135/105 | | 81/(-9) | | -4-3n+3=23 | | x=218+508 | | 3.6/y=10.8/12 | | 30.99-25= | | 5(8x-8)=440 | | 11-8x=1-6x | | 3(5y-4)+15=5(y-3)-(3y+2) | | 12+3x=24-3x | | -20m+20=-17m-13 | | 20=12x+3 | | 5/6=x/6 | | 9x+(-7)=8x | | 10c=-11-3(-3c+1) | | -8r=-3r+20 | | x/6=0,5 | | 14v-12+7w+(-4v)= | | 20-y+20=2y-20 | | 6-0.5x=15 | | 9x+(17)=8x | | 8h+8=4h | | 18.75=3u | | 459.90=210x+1.19x | | 4=29+13x | | 6c=-8+2c |